The effect of monensin sodium on lactational performance of autumn- and spring-calving cows : a thesis presented in partial fulfillment of the requirements for the degree of Masters of Agricultural Science in Animal Science at Massey University - Maas, James Arthur (Massey University, 1990)
The effects of monensin sodium, administered at the rate of 320 mg/day for 100 days by intraruminal controlled release capsule, on lactational performance and related parameters were examined in pasture-fed lactating dairy cows. The study was conducted in two seasons, with 60 autumn- and 60 spring-calving Friesian cows divided into two balanced groups, treatment and control. Responses were measured in terms of yield of milk, fat and protein, liveweight, condition score and plasma levels of insulin, glucose, β-hydroxybutyrate, urea and non-esterified fatty acids (NEFA). The effect of season and monensin treatment on ruminal digestion characteristics was measured in a single group of ruminally-fistulated castrated male sheep which were housed indoors in metabolism crates and fed fresh-cut autumn and spring pasture similar to that fed to the cows. Responses were assessed in terms of ruminal volatile fatty acid (VFA) molar proportions, ruminal ammonia and pH levels, feed apparent digestibility and nitrogen balance. Blood parameters, similar to those measured in the cows, were also evaluated. Autumn pasture had significantly lower proportions of water-soluble carbohydrate (P<0.05), cellulose (P<0.05) and lignin (P<0.05) and increased pectin (P<0.05), hemicellulose (P<0.05) and crude protein (P<0.10) levels when compared to spring pasture. Voluntary feed intake by sheep of autumn pasture was lower (P<0.001) than that of spring pasture and was significantly (P<0.05) reduced by monensin treatment. Monensin treatment significantly decreased the molar proportions of acetic acid (P<0.10) and butyric acid (P<0.001) and increased the molar proportions of propionic acid (P<0.001) and minor VFA's (P<0.01). Nitrogen retention of the sheep was significantly (P<0.05) reduced by monensin treatment. Plasma glucose levels were increased (P<0.10) by monensin treatment during the fourth 5-day collection period in both seasons. The monensin treatment did not significantly affect milk or milk component yield of the cows in either season. There was a trend towards increased milk and protein yield in monensin-treated cows of the spring-calving group but this difference did not attain statistical significance. The age x monensin treatment interaction was significant (P<0.05) for milk yield of spring-calving cows, 2- and 3-year old cows having increased milk yield as compared to the remaining age groups. The spring-calving cows had significantly (P<0.05) higher plasma urea levels when treated with monensin. The autumn-calving cows showed significantly (P<0.05) higher plasma glucose levels and reduced loss of body condition (P<0.10) in response to monensin treatment. Although monensin treatment altered ruminal VFA proportions in the sheep in a manner consistent with previous reports, these effects were not associated with improved lactational performance in the cows. Thus while monensin sodium administered by controlled release capsule may be a useful method of controlling bloat in cows it does not appear to give reliable responses in lactational performance.
Keywords: Dairy cattle; Milk production; Friesian cows; Monensin sodium